Bowel dysfunction following pullthrough surgery is associated with an overabundance of nitrergic neurons in Hirschsprung disease - Cheng, Lily S. (J Pediatr Surg, 2016)
PURPOSE: Recent evidence suggests that patients with Hirschsprung disease (HD) have abnormal neurotransmitter expression in the ganglionated proximal colon. These alterations may cause persistent bowel dysfunction even after pullthrough surgery. We sought to quantify the proportion of nitrergic neurons in the ganglionic colon of HD patients and relate these findings to functional outcome. METHODS: The proximal resection margin from 17 patients with colonic HD who underwent a pullthrough procedure and colorectal tissue from 4 age-matched controls were immunohistochemically examined to quantify the proportion of nitrergic neurons. The incidence of constipation, incontinence, and enterocolitis in HD patients was assessed retrospectively and correlated with the proportion of nitric oxide synthase (NOS) expressing neurons. Neuronal subtypes in the ganglionic colon of the Edrnb(−/−) mouse model of HD were also studied. RESULTS: Mice with HD had a significantly higher proportion of NOS+ neurons in ganglionic colon than normal littermates (32.0 ± 5.6% vs. 19.8 ± 1.2%, p<0.01). Patients with HD also had significantly more NOS+ neurons than controls (18.4 ± 4.6% vs. 13.1 ± 1.9%, p<0.01). Patients who experienced constipation or enterocolitis postoperatively tended toward a higher proportion of NOS+ neurons (21.4 ± 3.9% vs. 17.1 ± 4.1%, p=0.06). Furthermore, patients with a proportion of NOS+ neurons above the median of all HD patients (18.3%) were significantly more likely to have constipation than those below the median (75% vs. 14%, p<0.05). CONCLUSION: An overabundance of nitrergic neurons in the proximal resection margin is associated with HD and may predict bowel dysfunction following pullthrough surgery.